Carbonyl-anchored single-atom palladium achieved on waste printing paper-derived carbon material by impregnation method: remarkable performance in selective oxidation of benzyl alcohol. (March 2023) - Zhou, Y.; Ma, C.; Wang, X.; Xiang, Z.; Yin, C.; Yan, W.; He, W.; Liu, Y.; Lu, C.; Li, X.
Abstract: N element can form various forms of coordination with metals, so it is used in the preparation of single-atom catalysts widely. However, the strong coordination bond between N and metals will inhibit the catalytic activity of the metal atoms. In this work, the waste printing paper was used to prepare a new type of carbon material by calcining at high temperature in water vapor atmosphere (PC-900). The waste printing paper-derived carbon presented the only carbonyl groups, which resulted in the loading of palladium (Pd) as single atoms (Pd/PC-900). X-ray photoelectron spectroscopy characterization and density function theory simulation proved that the Pd atom coordinated with two carbonyl groups. In the oxidation of benzyl alcohol, the adsorption energy of benzyl alcohol on Pd single atom was higher than benzaldehyde. The reaction selectivity of Pd/PC-900 to benzaldehyde was over 99.3% and the reaction rate of Pd/PC-900 (TOF = 19.9 × 10 3 h −1 ) was about twice of conventional Pd/AC (TOF = 9.7 × 10 3 h −1 ) at 140 °C in 0.1 MPa oxygen. After four runs, the activity and selectivity of Pd/PC-900 remained unchanged. Several analysis methods demonstrated that benzyl alcohol was oxidized to benzaldehyde with the alternate catalysis of Pd 2+ and Pd 0 . Graphical abstract: Image 1 Highlights: Carbon-based single-atom catalyst was prepared by a impregnation method. The catalyst exhibited excellent catalytic performance for benzyl alcohol oxidation. Monoatomic Pd was stabilized on the carbon material by two carbonyl anchors. Investigations into the formation mechanism by DFT calculation and characterization. Waste printing paper-derived carbon-based single-atom catalyst was synthesized.